Photosynthetic and physiological responses of different peony cultivars to high temperature - Ji, Wen; Hong, Erman; Chen, Xia; Li, Zhijun; Lin, Bangyu; Xia, Xuanze; Li, Tianyao; Song, Xinzhang; Jin, Songheng; Zhu, Xiangtao (Frontiers in Plant Science, 2022)
In order to investigate the causes of the differences in heat tolerance (‘Lu He Hong’ and ‘Zhi Hong’), we studied the physiological changes, photosynthetic properties and regulatory mechanism of the two peony cultivars at high temperature. The results showed that the physiological changed of different peony cultivars varied significantly under high temperature stress. With the extension of high temperature stress time, MDA content of 'Lu He Hong' increased,while 'Zhi Hong' rised first and then decreased, SOD activity of 'Lu He Hong' rised first and then decreased, that of 'Zhi Hong' kept rising, POD activity of 'Lu He Hong' kept decreasing, while 'Zhi Hong' rised. The photosynthetic instrument records the change of peony photosynthesis parameters at high temperature; the chlorophyll A (Chla) fluorescence transient is recorded using the plant efficiency analyzer (PEA), analyzed according to the JIP test (O-J-I-P fluorescence transient analysis), and several parameters were derived to explain the photosynthetic efficiency difference between different peony cultivars. The tested cultivars responded differently to the survey conditions, and the PCA analysis showed that the ‘Zhi Hong’ was more well tolerated and showed better thermal stability of the PSII. The reduced efficiency of the ‘Lu He Hong’ PSII antenna leads to higher heat dissipation values to increase the light energy absorbed by unit reaction center (ABS/RC), the energy captured by unit reaction center (TR0/RC), and the energy dissipated by unit reaction center (DI0/RC), which significantly leads to its lower total photosynthetic performance (PItotal). The light capture complex of the variety ‘Zhi Hong’ has high connectivity with its reaction center, less damage to OEC activity, and better stability of the PSII system. The results show that ‘Zhi Hong’ improves heat resistance by stabilizing the cell membrane, a strong antioxidant system, as well as a more stable photosynthetic system. The results of this study provide a theoretical basis for the screening of heat-resistant peonies suitable for cultivation in Jiangnan area and for the selection and breeding of heat-resistant cultivars.